2019
DOI: 10.1002/ecs2.2970
|View full text |Cite
|
Sign up to set email alerts
|

Life in a contaminant milieu: PPCP mixtures generate unpredictable outcomes across trophic levels and life stages

Abstract: Nearly all aquatic ecosystems are affected by sublethal levels of anthropogenic chemical contamination, but other agents of large‐scale anthropogenic disruption of ecosystems have received more attention. Consequently, ecologists do not fully appreciate how sublethal contaminant exposure affects ecosystems. Sublethal contaminants can affect ecological systems directly via their impacts on an organism's fitness or indirectly by changing the strengths of species interactions. This study investigated how an emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Community‐level and/or meso‐ or microcosm studies with multiple species have been done to track the effects of API mixtures on survival, biomass, biodiversity, and richness across trophic levels (Pomati et al, 2017; Roose‐Amsaleg et al, 2021). Though not with APIs, Parrish et al (2019) showed that density‐dependent processes that regulate predator–prey dynamics among mosquitofish (predator) and mosquito larvae (prey) were differentially affected by exposure to individual PPCPs (caffeine, diethyltoluamide, and triclosan) and their mixture. In addition, environmental DNA has been used to investigate the influence of binary PPCP mixtures on bacterial ecological functions (e.g., denitrification and ammonium oxidation) in river sediment (Xu et al, 2020).…”
Section: What Are the Advances In Our Understanding Of The Ecotoxicol...mentioning
confidence: 99%
“…Community‐level and/or meso‐ or microcosm studies with multiple species have been done to track the effects of API mixtures on survival, biomass, biodiversity, and richness across trophic levels (Pomati et al, 2017; Roose‐Amsaleg et al, 2021). Though not with APIs, Parrish et al (2019) showed that density‐dependent processes that regulate predator–prey dynamics among mosquitofish (predator) and mosquito larvae (prey) were differentially affected by exposure to individual PPCPs (caffeine, diethyltoluamide, and triclosan) and their mixture. In addition, environmental DNA has been used to investigate the influence of binary PPCP mixtures on bacterial ecological functions (e.g., denitrification and ammonium oxidation) in river sediment (Xu et al, 2020).…”
Section: What Are the Advances In Our Understanding Of The Ecotoxicol...mentioning
confidence: 99%
“…Synthetic organic chemicals are typically present at low environmental concentrations in the aquatic environment (pg/L to ng/L) and are therefore often called micropollutants (Schwarzenbach et al, 2006). Micropollutants often have deleterious effect at different trophic levels (Beketov et al, 2013; Burdon et al, 2020; Kidd et al, 2007; Parrish et al, 2019) and levels of biological organisation (Inostroza et al, 2016; König et al, 2017; Weichert et al, 2020) due to their high biological activity (Stamm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%